Establishment of the broad outlines of state policy as a development - JS Panjaitan, Marojahan (Opción, 2019)
This research tries to find the legal basis for MPR (People’s Consultative Assembly) and the President granting authority in determining the GBHN (Broad Outlines of State Policy) via analytical descriptive research. As a result, the development program must be carried out on an ongoing basis, in which the program is contained in the GBHN. In conclusion, as a legal basis for drafting and determining the GBHN, it can refer to Article 8 paragraph (1) and (2) of the Act. No. 12 of 2012.